2019
DOI: 10.14712/23362936.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Dasatinib

Abstract: Tyrosine kinase inhibitors have recently become an essential tool in management of chronic myeloid leukaemia (CML). Dasatinib, a representative of those drugs, acts by inhibiting key proteins included in CML development, predominantly Bcr-Abl and Src. Its advantage is that it shows activity in many cases where other agents bring no improvement due to resistance. Pharmacokinetics of dasatinib has specific characteristics that may play an important role in achieving sufficient exposure in patients. Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Dasatinib and nilotinib have been investigated in hematopoietic malignancies and inhibit plateletderived growth factor-β receptor signaling, ephrin receptor kinases and mast/stem cell growth factor receptor (23). Dasatinib has also been shown to inhibit sarcoma tyrosine kinase (SRC) family kinases, a major means of resistance to anti-HER2 therapy in patients with breast cancer (24)(25)(26).…”
mentioning
confidence: 99%
“…Dasatinib and nilotinib have been investigated in hematopoietic malignancies and inhibit plateletderived growth factor-β receptor signaling, ephrin receptor kinases and mast/stem cell growth factor receptor (23). Dasatinib has also been shown to inhibit sarcoma tyrosine kinase (SRC) family kinases, a major means of resistance to anti-HER2 therapy in patients with breast cancer (24)(25)(26).…”
mentioning
confidence: 99%
“…Dasatinib, quercetin, and fisetin are the most well-studied senolytic agents [22]. Dasatinib is a secondgeneration tyrosine kinase inhibitor that is used for the treatment of CML and AML [23]. Quercetin is a polyphenolic flavonoid compound with antioxidant properties, which exerts preventive effects for various diseases, such as osteoporosis, some forms of cancer, tumors, and lung and cardiovascular diseases [24].…”
Section: Senolytic Agentsmentioning
confidence: 99%
“…Dasatinib is rapidly absorbed following oral administration with time to C max (T max ) ranging from 0.5 to 6 h ( European Medicines Agency, 2006 ). With the emergence of more studies, T max values observed among subjects ranged from 0.28 to 6.3 h ( Horinkova et al, 2019 ). The oral bioavailability was rather low in preclinical studies with values ranging from 45 to 51% ( Luo et al, 2006a ), whereas other studies showed bioavailability from 14 to 34% ( Kamath et al, 2008b ).…”
Section: Pharmacokinetics Variabilitymentioning
confidence: 99%
“…Dasatinib is metabolized in humans, primarily by CYP3A4, and flavin-containing monooxygenase 3 (FMO-3) and uridine diphosphate-glucuronosyltransferase (UGT) enzymes are also involved in the formation of dasatinib metabolites ( Bristol-Myers Squibb, 2017 ). Routes of metabolism include hydroxylation, N-dealkylation, N-oxidation, alcohol oxidation and direct glucuronide or sulphate conjugation ( Horinkova et al, 2019 ). There are five phase I circulating metabolites: M4, M5, M6, M20 and M24, among which M20 and M24 represent 45 and 25% of the AUC 0-24 of dasatinib, respectively.…”
Section: Pharmacokinetics Variabilitymentioning
confidence: 99%